Reputation and Hierarchy in Dynamic Models of Employment - MacLeod, W. Bentley; Malcomson, James M. (Journal of Political Economy, 1988)
The employment relationship with employees' ability and their actions both private information (thus combining adverse selection with moral hazard) is modeled as a repeated game with self-enforcing contracts being perfect Bayesian Nash equilibria. Under termination contracts, the equilibrium contract structure consists of a hierarchy of ranks, finite in number even though ability is continuous. Reputation acts as an effective device for worker discipline without the need for involuntary unemployment. Selection by bonding is not, in general, incentive compatible, but selection by promotion of employees through the ranks is. Many other features correspond to observed employment structures.